A mycovirus modulates the endophytic and pathogenic traits of a plant associated fungus - Zhou, Lingling; Li, Xuepei; Kotta-Loizou, Ioly; Dong, Kaili; Li, Shifang; Ni, Dejiang; Hong, Ni; Wang, Guoping; Xu, Wenxing (The ISME Journal, 2021)
Fungi are generally thought to live in host plants with a single lifestyle, being parasitism, commensalism, or mutualism. The former, known as phytopathogenic fungi, cause various plant diseases that result in significant losses every year; while the latter, such as endophytic fungi, can confer fitness to the host plants. It is unclear whether biological factors can modulate the parasitic and mutualistic traits of a fungus. In this study, we isolated and characterized a mycovirus from an endophytic strain of the fungus Pestalotiopsis theae , a pathogen of tea ( Camellia sinensis ). Based on molecular analysis, we tentatively designated the mycovirus as Pestalotiopsis theae chrysovirus-1 (PtCV1), a novel member of the family Chrysoviridae , genus Alphachrysovirus . PtCV1 has four double-stranded (ds) RNAs as its genome, ranging from 0.9 to 3.4 kbp in size, encapsidated in isometric particles. PtCV1 significantly reduced the growth rates of its host fungus in vitro (ANOVA; P -value < 0.001) and abolished its virulence in planta (ANOVA; P -value < 0.001), converting its host fungus to a non-pathogenic endophyte on tea leaves, while PtCV1-free isolates were highly virulent. Moreover, the presence of PtCV1 conferred high resistance to the host plants against the virulent P. theae strains. Here we report a mycovirus that modulates endophytic and phytopathogenic fungal traits and provides an alternative approach to biological control of plant diseases caused by fungi.